Acceleration of lithotripsy using cavitation bubbles induced by second-harmonic superimposition. (21st June 2016) - Osuga, Masamizu; Yasuda, Jun; Jimbo, Hayato; Yoshizawa, Shin; Umemura, Shin-ichiro
Abstract: Shock wave lithotripsy potentially produces residual stone fragments too large to pass through ureters and significant injury to the normal tissue surrounding the stone. Previous works have shown that the collapse of cavitation bubbles induced by high-intensity focused ultrasound can produce small stone fragments via cavitation erosion. However, the erosion rate is hypothesized to be reduced by ultrasound attenuation by excessively generated bubble clouds. If so, it is important to generate the bubbles only on the stone surface. The effects of peak-negative-enhanced (PNE) and peak-positive-enhanced (PPE) waves obtained by second-harmonic superimposition were investigated to control cavitation bubbles. With the PNE waves, the bubbles were generated only on the stone surface and the maximum erosion rate was 232 ± 32 mg/min. All the fragments were smaller than 2 mm, which makes them pass through ureters naturally. The proposed method shows the potential to significantly improve the speed of lithotripsy.